A Case Report of Bardet Biedl Syndrome in a Patient from Pakistan who Presented with Osmotic Symptoms associated with Diabetes Mellitus - Bakht Babar; Muqsit Ali Shaukat; Misbah Manzoor; Samina Bibi; Hashim Khan (International Journal of Medical Students, 2024)
Background: The primary features of Bardet Biedl syndrome (BBS) are characterized by retinal degeneration, central obesity, post-axial polydactyly, intellectual impairment, hypogonadism, and renal anomalies. The secondary clinical features are syndactyly, delay in the achievement of developmental milestones, diabetes insipidus, diabetes mellitus, congenital heart disease and liver involvement. It is diagnosed when a patient has either four primary or three primary and two secondary clinical features and the management depends upon those predominant features.